Do plants need passport?: a socio-economic study of the role of exotic tree and other plants species in Quang Tri province, Vietnam - Midgley, S.J.; Byron, R.N.; Chandler, F.C.; Ha Huy Thinh; Tran Hung Son; Hoang Hong Hanh (Commonwealth Scientific and Industrial Research Organisation, 1997)
A multidisciplinary team evaluated the role and use of exotic and indigenous trees in household livelihood systems in four villages, typical of three distinctly different ecosystems in Quang Tri Province, central Viet Nam. While in each case farmers used a great variety of trees and plants to meet their diverse subsistence and cash needs, this study reveals the crucial contribution of exotic trees. Where land tenure is clear and ownership of the trees is unambiguous, there was widespread enthusiasm for tree planting in all four areas studied. The use of casuarinas on sand dune areas as a coastal protection belt, for farm windbreaks and agroforestry, seems entirely positive on all social, ecological and economic criteria. Likewise the use of acacias provided significant economic and environmental benefits as an essential windbreak around (exotic) coffee and pepper plantations in the highlands near the Laos border, and in mixed plantations on farms in the low hills as a component of a mosaic landscape. Small-scale eucalyptus planting for local fuelwood and construction materials in the foothills has no discernible social or ecological ill-effects, offers one of the few economically viable land use options for both women and men, and creates a low-cost alternative to collection of wood from the few remaining natural forests. Through consultation between local villagers, government forestry extension workers, NGO assistance programmes, and other land users, appropriate species and silvicultural systems are being developed to significantly enhance social and economic welfare with minimal adverse environmental impact. The farmers concluded that provided the trees meet their needs, they do not care about the country of origin of that species.